Health literacy and physical and mental health status in octogenarian patients with coronary artery disease - a prospective cohort multicentre study. (2nd July 2022) - Instenes, I; Brors, G; Hjertvikrem, N; Allore, H; Borregaard, B; Deaton, C; Larsen, A I; Osborne, R; Palm, P; Thompson, D R; Norekval, T M
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): MTG Holding AS Introduction: The number of octogenarians (≥80 years of age) receiving percutaneous coronary intervention (PCI) is rising. Evidence supports that PCI improves quality of life and functional status in this group. Optimal health-promoting behaviour is strongly influenced by health literacy. However, there is limited knowledge about the association between health literacy, physical and mental health status in octogenarians. Purpose: To determine if octogenarians health literacy is associated with generic and disease-specific physical and mental health status after PCI. Methods: A prospective cohort study recruited 3417 participants from seven Danish and Norwegian PCI centres, and was conducted from June 2017 until May 2019. Multiple linear regression analysis was used. Health literacy was assessed by four of the nine scales from the Health Literacy Questionnaire (HLQ) (were higher score are better); "Social support for health" (scale range 1-4) "Appraisal of health information", (scale range 1-4) "Ability to find good health information" (scale range 1-5) and "Understand health information well enough to know what to do" (scale range 1-5). Generic physical and mental health status was assessed with RAND-12 at baseline (scale range 0-100, were higher score are better). After two months, disease-specific physical and mental health status was assessed with Myocardial Infarction Dimensional Assessment Scale (scale range 0-100, were lower score are better). Socio-demographic (age, gender, cohabitation status, education) and clinical variables (number of comorbidities) were included as covariates. Results: In all, 318 octogenarians with mean age 83.4 years (range 80-96) participated, of which 69% were males. Three aspects of health literacy, "Social support for health", "Ability to find good health information" and "Understand health information well enough to know what to do", were significantly associated with health status. Specifically, for a unit increase of "Social support for health", the generic mental health status increased by 3 units (B: 3.0 [0.2 to 5.8] P=0.034). Further, a unit increase of "Ability to find good health information" was associated with a significant 4.2 higher disease-specific physical health and significant 5.3 higher disease-specific mental health (B:-4.2 [-8.0 to -0.4] P=0.029, B:-5.3 [-9.0 to -1.6] P=0.005, respectively). Finally, for a unit increase of "Understand health information well enough to know what to do" the disease-specific physical health improved by 5.1 units (B:-5.1 [-9.7 to -0.5] P=0.029) and disease-specific mental health improved by 5.2 units (B:-5.2 [-9.7 to -0.7] P=0.025). Conclusion: In this study, we found that elements of health literacy were associated with both physical and mental health status in octogenerians. These findings highlight the importance of adequate health literacy and the need to support those with lower health literacy following PCI.